Indonesia Pelatihan Peningkatan Kompetensi Guru SD Dalam Penggunaan Internet Berbasis Metode E-Learning SD Negeri Kecamatan Tualang Kabupaten Siak - Suarman Suarman; M.Yogi Riyantama Isjoni Isjoni; Mifta Rizka Rizka; Filma Alia Sari; Henny Indrawati; Caska Caska (Journal of Community Engagement Research for Sustainability, 2022)
In the 4.0 revolution era, teachers are required to have competencies and abilities that are in accordance with the demands of the times. Learning is not limited to face-to-face meetings between teachers and students in the classroom. The teaching and learning process can be done anywhere and anytime using the internet. This activity aims to improve teacher competence in using the internet based on the E-Learning method. This activity is carried out in 3 stages, namely the preparation stage, the implementation stage and the evaluation stage. The preparatory stage is carried out by collecting data on elementary school teachers in Tualang District, making observations, giving permission to the training site, preparing the place and training materials. The implementation stage is carried out in two stages, namely the introduction of E-Learning-based learning with demonstration, discussion and question and answer methods and practicing E-Learning-based online learning. The results of the service activities show an increase in teacher competence in using the internet based on E-Learning. The evaluation and follow-up stages are carried out by evaluating the organizers and evaluating the participants. The training participants who took part in this activity were quite enthusiastic about participating in the material and conducting simulations. It is expected that participants who take part in training activities can manage learning using the internet based on the E-Learning method.